Kinematics of take-off phase in successful and unsuccessful performances of gymnastic somersault: an experimental study - Horri, Z.; Lenjannejadian, S.; Boroujeni, M. R.; Farazin, A. (Sport Sciences for Health, 2022)
Purpose Kinematic variables identify movement patterns and are used to compare successful versus unsuccessful performances that cause to better understanding of performance optimization techniques. Therefore, the aim of this study was to compare the angular kinematic variables in successful and unsuccessful performances in gymnastic somersault for identifying the optimization performance of this technique.